The Effects of Infrastructure Development on Growth and Income Distribution - Calderón, César; Servén, Luis (World Bank, Washington, D.C., 2013)
The authors provide an empirical evaluation of the impact of infrastructure development on economic growth and income distribution using a large panel data set encompassing over 100 countries and spanning the years 1960-2000. The empirical strategy involves the estimation of simple equations for GDP growth and conventional inequality measures, augmented to include, among the regressors, infrastructure quantity and quality indicators, in addition to standard controls. To account for the potential endogeneity of infrastructure (as well as that of other regressors), the authors use a variety of generalized-method-of-moments (GMM) estimators based on both internal and external instruments and report results using both disaggregated and synthetic measures of infrastructure quantity and quality. The two robust results are: (1) growth is positively affected by the stock of infrastructure assets, and (2) income inequality declines with higher infrastructure quantity and quality. A variety of specification tests suggests that these results do capture the causal impact of the exogenous component of infrastructure quantity and quality on growth and inequality. These two results combined suggest that infrastructure development can be highly effective to combat poverty. Furthermore, illustrative simulations for Latin American countries suggest that these impacts are economically quite significant, and highlight the growth acceleration and inequality reduction that would result from increased availability, and quality of infrastructure.